Air-water CO2 and water-sediment O2 exchanges over a tidal flat in Tokyo Bay - Tokoro, Tatsuku; Kuwae, Tomohiro (Frontiers in Marine Science, 2022)
Despite the potential for carbon storage in tidal flats, little is known about the details of relevant processes because of the complexity of intertidal physical and chemical environments and the uniqueness of the biota. We measured air-water carbon dioxide (CO2) fluxes and water-sediment oxygen (O2) fluxes over a tidal flat in Tokyo Bay by the eddy covariance method, which has the potential to facilitate long-term, broad-scale, continuous monitoring of carbon flows in tidal flats. The results indicated that throughout the tidal flat in Tokyo Bay, CO2 was taken up from the atmosphere at a rate of 6.05 ± 7.14 (mean ± SD) mmol m−2 hour−1, and O2 was taken up from the water into the sediment at a rate of 0.62 ± 1.14 (mean ± SD) mmol m−2 hour−1. The fact that the CO2 uptake rate was about 18 times faster than the previously reported average uptake rate in the whole area of Tokyo Bay was attributable to physical turbulence in the water column caused by bottom friction. Statistical analysis suggested that light intensity and water temperature were the major factors responsible for variations of CO2 and O2 exchange, respectively. Other factors such as freshwater inputs, atmospheric stability, and wind speed also affected CO2 and O2 exchange. High rates of O2 uptake from the water into the sediment surface and high rates of atmospheric CO2 uptake into the water column occurred simultaneously (R2 = 0.44 and 0.47 during day and night, respectively). The explanation could be that photosynthetic consumption of CO2 and production of O2 in the water column increased the downward CO2 (air to water) and O2 (water to sediment) fluxes by increasing the concentration gradients of those gases. Resuspension of sediment in the low-O2 layer by physical disturbance would also increase the O2 concentration gradient and the O2 flux in the water.